2019
DOI: 10.3390/ijerph16193582
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Meta-Analyses: The Impact of Dietary Lifestyle on Stroke Risk

Abstract: A stroke is one of the most prevalent cardiovascular diseases worldwide, both in high-income countries and in medium and low-medium income countries. The World Health Organization’s (WHO) report on non-communicable diseases (NCDs) indicates that the highest behavioral risk in NCDs is attributable to incorrect nutrition. The objective of our work is to present an overview of meta-analyses that have investigated the impact of different foods and/or drinks in relationship with the risk of stroke events (ischemic/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…It is known that making lifestyle changes (nutrition, smoking habits, physical activity, alcohol, etc.) can radically change not only one's cardiovascular risk profile, but also the metabolic and oncological health of the individual [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that making lifestyle changes (nutrition, smoking habits, physical activity, alcohol, etc.) can radically change not only one's cardiovascular risk profile, but also the metabolic and oncological health of the individual [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…A decisive role could be played by family doctors in identifying high-risk patients, promoting their control through ultrasound screening, and making people aware of taking action on modifiable risk factors relating to lifestyles [ 38 ], with particular reference to smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of looking at individual nutrients or foods, pattern analysis examines the effects of overall diet and represents a broader picture of food and nutrient consumption, and maybe more predictive of disease risk than individual foods or nutrients [ 46 ]. It has also been demonstrated that the highest behavioral risk is incorrect nutrition for noncommunicable diseases, and that the choice of a balanced diet can reduce the risk of stroke [ 47 ].…”
Section: E Pidemiological and Observational Studiesmentioning
confidence: 99%